PEA guidelines for impact study and operation of DG for islanding operation - Fuangfoo, Pradit; Meenual, Thongchai; Lee, Wei Jen; Chompoo-Inwai, Chow (My University, 2008)
Intentional islanding operation of distributed generation (DG) can increase system reliability and reduce customer outage costs. Guidelines for the impact study and operation of DG for islanding operation should be implemented. The Provincial Electricity Authority (PEA) plays more attention to intentional islanding operation. To perform islanding operation, PEA has established islanding operation and impact study guidelines for DG. This paper presents the development of these guidelines. A case study was conducted to demonstrate the results of both steady-state and dynamic analyses. Operational issues are also taken into account in this paper. © 2008 IEEE.
Keywords: Distributed generation (DG); Dynamic performance; Guidelines; Impact study